Unrecognizable, abandoned, unnamed, avoided places: On the murders committed against Jews in Poland in the period after the Second World War and their commemoration - Rykała, Andrzej (European Spatial Research and Policy, 2021)
The fall of the Third Reich, turning the “most tragic page” in the history of the Jewish nation, i .e . the Second World War, did not mean the end of the tragedy for Jews on Polish soil. Even before the end of the greatest conflict in the history of humankind, in the areas liberated from Nazi Germany occupation, many survivors of the Holocaust experienced acts of ruthless violence. However, very few of the numerous victims of the post-war anti-Jewish terror have been commemorated in public space. To a very small extent the form of public commemoration also covered earlier wartime cases of collective murders committed against Jews by Polish Christians. Even if the sites of the dramatic events which occurred in the shadow of the Holocaust were marked, the complete truth about their course was not restored everywhere.